Pengaruh role overload terhadap organizational citizenship behavior melalui emotional exhaustion dan dimoderasi oleh supervisor autonomy support - Aprilia Nindy Fatmawati; Dwiarko Nugrohoseno (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2023)
This study aims to determine and explain the effect of role overload on organizational citizenship behavior through emotional exhaustion and moderated by supervisor autonomy support for employees of PT X Mojokerto. This research is a causality study using a quantitative approach. The sampling technique used a saturated sample with a total sample of 112 employees of the Circular Loom division of PT X. The statistical analysis used in this study is Partial Least Square (PLS) with the help of WarpPLS 8.0 software.The results of the study explain that role overload has a significant positive effect on organizational citizenship behavior, role overload has a significant positive effect on emotional exhaustion, emotional exhaustion has a positive but not significant effect on organizational citizenship behavior, emotional exhaustion mediates the influence of role overload on organizational citizenship behavior, supervisor autonomy support does not moderate the relationship between role overload and organizational citizenship behavior through emotional exhaustion.The implication of this research that can be applied to PT X Mojokerto is optimizing the form of appreciation or reward for employees who are willing to implement organizational citizenship behavior even when employees experience workload demands and emotional exhaustion for the progress of the company's business.